2014
DOI: 10.1002/anie.201400001
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Encoding Photoswitchable Click Amino Acids in Escherichia coli and Mammalian Cells

Abstract: The ability to reversibly control protein structure and function with light would offer high spatiotemporal resolution to investigate biological processes. To enable photoresponsiveness to general proteins, we genetically incorporated into proteins a set of photoswitchable click amino acids (PSCaas), which contain both a reversible photoswitch and an additional click functional group for further modifications. Orthogonal tRNA-synthetases were evolved to genetically encode PSCaas bearing azobenzene and alkene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 53 publications
2
81
0
Order By: Relevance
“…22,32,33 A new “small-intelligent” mutagenesis approach, which uses a single codon for each amino acid, was then devised to generate mutant PylRS libraries enabling a greater number of residues simultaneously randomized, from which mutants were identified to incorporate Uaas with bulky conjugated rings 34 and even Uaas containing long azobenzene side chains (Figure 3C). 35,36 These results and data from other groups 37 suggest unexpectedly high flexibility in engineering aaRS substrate specificity. As the tRNACUApyl/PylRS can be used in both prokaryotic and eukaryotic cells, these evolved PylRS mutants enable diverse Uaas to be incorporated in various cells and organisms.…”
Section: Introductionmentioning
confidence: 52%
“…22,32,33 A new “small-intelligent” mutagenesis approach, which uses a single codon for each amino acid, was then devised to generate mutant PylRS libraries enabling a greater number of residues simultaneously randomized, from which mutants were identified to incorporate Uaas with bulky conjugated rings 34 and even Uaas containing long azobenzene side chains (Figure 3C). 35,36 These results and data from other groups 37 suggest unexpectedly high flexibility in engineering aaRS substrate specificity. As the tRNACUApyl/PylRS can be used in both prokaryotic and eukaryotic cells, these evolved PylRS mutants enable diverse Uaas to be incorporated in various cells and organisms.…”
Section: Introductionmentioning
confidence: 52%
“…A photogaged cysteine was likewise incorporated into the Kir2.1 potassium channel to create a photoinducible inwardly rectifying potassium (PIRK) channel, which can be used to optically suppress neuronal firing [32]. Moreover, photoswitchable click amino acids (PSCaas), which contain of an azobenzene photo switch and a click functional group, can also be used to create a covalent protein bridge between the site of incorporation and a nearby cysteine residue in situ [33, 34]. Because the azobenzene moiety undergoes cis-trans photoisomerization, a PSCaa-mediated protein bridge can be used to optically control protein conformation.…”
Section: Optically Inducible Toolsmentioning
confidence: 99%
“…This hybrid photoswitchable amino acid is then coupled to pdCpA and ligated to a modified tRNA lacking two terminal nucleotides, followed by in vitro translation using mRNA. Recently, it has been demonstrated that the successful incorporation of a photochromic amino acid with a second reactive group can undergo addition to another nearby site on the protein [70]. This approach allows for the formation of another attachment site, or cross-linking to the protein, giving the user the opportunity to make larger scale changes to the protein backbone and secondary structure.…”
Section: Genetically Encoded Amino Acidsmentioning
confidence: 99%
“…(b) Reaction with a nucleophile is possible to prepare cross-linked photochromic amino acids[70]. 11 Structures of attached photochromic groups: (1) trityl-substituted azobenzene,(2) maleimide-substituted azobenzene, and(3)spiropyran[71].…”
mentioning
confidence: 99%